2020
DOI: 10.12659/msm.918933
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of Interleukin-36 Receptor Protected Cardiomyocytes from Ischemia-Reperfusion Injury in Cardiopulmonary Bypass

Abstract: Background: Interleukin-36 has been demonstrated to be involved in inflammatory responses. Inflammatory responses due to ischemia-reperfusion injury following cardiopulmonary bypass (CPB) can cause heart dysfunction or damage. Material/Methods: The CPB models were constructed in IL-36R-/-, IL-36RN-/-, and wild-type SD rats. Ultrasonic cardiography and ELISA were used to evaluate the cardiac function and measuring myocardial biomarker levels in different groups. TUNEL assay was used to evaluate apoptosis. Weste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
2
5
0
Order By: Relevance
“…Importantly, this decrease was evident in both adult and more damaged aged hearts. Our data support the recent observation of reduced oxidative stress, measured using spectrophotometry of superoxide dismutase and malondialdehyde activity, in IL-36R–knockout rats undergoing cardiopulmonary bypass ( 51 ). However, we further detail that the antioxidant effects of IL-36Ra occur specifically on both coronary endothelial cells and cardiomyocytes.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Importantly, this decrease was evident in both adult and more damaged aged hearts. Our data support the recent observation of reduced oxidative stress, measured using spectrophotometry of superoxide dismutase and malondialdehyde activity, in IL-36R–knockout rats undergoing cardiopulmonary bypass ( 51 ). However, we further detail that the antioxidant effects of IL-36Ra occur specifically on both coronary endothelial cells and cardiomyocytes.…”
Section: Discussionsupporting
confidence: 92%
“…However, our finding that IL-36Ra not only was vasculoprotective but also, importantly, remained beneficial in the setting of an age-related heightened inflammation in the coronary microvessels makes it a candidate worth pursuing clinically in elderly patients undergoing PCI for MI. In support of this is the recent work by Luo and colleagues, who demonstrated experimentally that deficiency of IL-36R protected cardiomyocytes in the setting of cardiopulmonary bypass ( 51 ).…”
Section: Discussionmentioning
confidence: 75%
“…Another study by Mutlu-Turkoglu et al [45] demonstrated that MDA level was increased and FRAP level was decreased in the CAD group compared to the control group. The results of a study by Luo et al [46] confirmed that IL-36R deficiency in cardiomyocytes repressed infiltration of bone marrow-derived inflammatory cells and oxidative stress, thus protecting cardiomyocytes and improving cardiac function in the cardiopulmonary bypass model rats. In conclusion, our study demonstrated that the higher serum levels of IL-36 and its association with the serum levels of TNF-α, IL-32, and IL-6 may play a key role in the CAD pathogenesis, leading to an increased risk of clogged arteries and oxidative stress.…”
Section: Discussionmentioning
confidence: 78%
“…Our results support previous reports demonstrating that cardiomyocytes express nNOS [ 90 ], specifically in the sarcoplasmic reticulum [ 18 , 109 ] and at the sarcoplasm membrane [ 104 ]. eNOS is detectable in spatial microdomains of plasma membrane, such as caveolae and lipid rafts and at the sarcoplasmic membrane [ 25 , 59 , 115 ], and iNOS is normally expressed under physiological conditions in the cardiomyocyte cytoplasm, perinuclear space, Golgi complex, contractile fibers, but not in the sarcoplasmic reticulum [ 4 , 5 , 10 12 , 57 , 90 ]. The second approach was using pharmacological agents at the IC 50 and thus specifically inhibiting only one NOS isoform.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, NO also modifies protein activity by reacting with specific sulfur moieties from cysteine residues, forming S -nitrosylations (SNOs) [ 69 , 93 , 110 ]. The cardiac production of NO is mediated by one of three NO synthase isoforms expressed under normal conditions: neuronal (nNOS), inducible (iNOS) or endothelial (eNOS) [ 10 , 30 , 57 , 69 , 88 , 105 , 109 , 110 ]. The three isoforms are expressed differentially and heterogeneously, varying in intensity and location between ventricles and in each muscle layer of the ventricle [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%